2020
DOI: 10.1039/c9nr07359k
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging of individual virion-triggered cortical actin dynamics for human immunodeficiency virus entry into resting CD4 T cells

Abstract: Using QD-encapsulated HIV particles and single-virus tracking, we revealed virus-regulated cortical actin dynamics during HIV entry into CD4 T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…By imaging quantum dots (QDs) containing viral particles with DiD-labeled viral membranes, the group of Zongqiang Cui observed that in CD4+ T lymphocytes and CEM-ss, the DiD and QD fluorescence signals separated at the cell surface. The DiD signal disappeared, while the QDs moved rapidly into the host cell cytosol, suggesting viral entry after fusion with the plasma membrane [54].…”
Section: Fusion With the Plasma Membranementioning
confidence: 99%
See 1 more Smart Citation
“…By imaging quantum dots (QDs) containing viral particles with DiD-labeled viral membranes, the group of Zongqiang Cui observed that in CD4+ T lymphocytes and CEM-ss, the DiD and QD fluorescence signals separated at the cell surface. The DiD signal disappeared, while the QDs moved rapidly into the host cell cytosol, suggesting viral entry after fusion with the plasma membrane [54].…”
Section: Fusion With the Plasma Membranementioning
confidence: 99%
“…Tracking of QDs-containing HIV-1 in primary macrophages expressing eGFP-Lifeact (F-actin labeling) showed accumulation of F-actin at the site of the viral fusion, followed by generation of a pore-like channel made of cortical actin, allowing the virion to enter the host cell cytoplasm. During channel formation, this site was enriched in α-actinin [54]. In Heladerived cells, HIV-1 viruses moved along actin filaments at the cell periphery and their movements were blocked by actin polymerization inhibitors, suggesting a role of actin in HIV-1 transport [44].…”
Section: Journey Toward the Nucleusmentioning
confidence: 99%
“…QDs encapsulated fluorescent virus particles and SVT helped to unravel that the individual HIV viruses could regulate subtle rearrangement in the cortical actin barrier, which opens a door and promotes virus entry (Yin et al, 2020). Actin binding protein, α‐actinin, performs an essential role in the dynamics of actin when HIV enters living cells.…”
Section: Applications Of Nanotechnology In Virus Tracking and Virus Infection Mechanism Researchmentioning
confidence: 99%
“…It also intensely localizes to and participates in the assembly of actomyosin contractile rings to drive membrane movements associated with yeast cytokinesis 3 . Recent evidence has shown that α-actinin aggregates at the entry site of Human Immunodeficiency Virus (HIV) to CD4 + T cells in order to regulate actin cortex rearrangements during membrane fusion, making αactinin a potential target for antiviral therapy 4 . Fascin, another key actin crosslinker, on the other hand, is predominantly present at the cell leading edge.…”
Section: Introductionmentioning
confidence: 99%